2020
DOI: 10.1021/acs.jafc.0c00387
|View full text |Cite
|
Sign up to set email alerts
|

Current Progresses on Monochloropropane Diol Esters in 2018–2019 and Their Future Research Trends

Abstract: The fatty acid esters of monochloropropane diol (MCPD) are a group of food source contaminants formed during thermal processing. These components were recognized as potential food source toxicants in the past few decades, and growing evidence has proven their toxic effects, especially to kidneys and testes. Therefore, increasing research articles reported their results about MCPD esters in recent years. In this perspective, a total of 35 research articles/reviews about MCPD esters, including the studies concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Apart from ecological impacts, issues on the effect of palm oil on public health have continued to be present in the past decades. Palm oil contaminants, such as 3-monochloropropane-1,2-diol esters (3-MCPDE) and glycidyl esters (GE), can pose possible risks to human health (EFSA, 2016;Gao et al, 2020;O'Brien, 2008;Sulin et al, 2020). Moreover, mineral oil hydrocarbon (MOH) contaminant such as mineral oil saturated hydrocarbons (MOSH) and mineral oil aromatic hydrocarbons (MOAH) found in oil palm fruits during processing at mills, has carcinogenic and genotoxic constituents, which can cause harmful consequences on overall health (Ahmad et al, 2019;Sdrigotti et al, 2021).…”
Section: P R E S Smentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from ecological impacts, issues on the effect of palm oil on public health have continued to be present in the past decades. Palm oil contaminants, such as 3-monochloropropane-1,2-diol esters (3-MCPDE) and glycidyl esters (GE), can pose possible risks to human health (EFSA, 2016;Gao et al, 2020;O'Brien, 2008;Sulin et al, 2020). Moreover, mineral oil hydrocarbon (MOH) contaminant such as mineral oil saturated hydrocarbons (MOSH) and mineral oil aromatic hydrocarbons (MOAH) found in oil palm fruits during processing at mills, has carcinogenic and genotoxic constituents, which can cause harmful consequences on overall health (Ahmad et al, 2019;Sdrigotti et al, 2021).…”
Section: P R E S Smentioning
confidence: 99%
“…Recent studies on 3-MCPDE and GE have demonstrated the possible risk of palm oil contaminants to human health (EFSA 2016;Gao et al, 2020;O'Brien, 2008;Sulin et al, 2020). Palm oil has a higher potential to produce these contaminants during the refining process, like almost all other oils and fats, although at generally lower levels (Hinrichsen, 2016).…”
Section: Nutritional Benefits Of Palm Oil Consumptionmentioning
confidence: 99%
“…with the latest food safety legislations and quality standards. Pertinent issues related to 3-MCPDE and GE in processed edible oils continues to dwell amongst edible oil processors and food regulators for more than a decade as evidenced from an increase in research works related to toxicity impacts, mechanistic pathways, analytical methods and mitigation strategies (Gao et al, 2020). The time has come for the EC to mandate the regulation of 3-MCPDE and GE thresholds in edible oils and fats with an effective date of 1 January 2021 (Commission Regulation (EU) 2020/1322, 2020).…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
“…A reduction of 86% in GE content was prevailed when the refined oil underwent post-refining trials at lower deodourisation temperature in the absence of degumming stage and reduced dosage of acid activated clay. Gao et al (2020) highlighted the importance of integrating three mitigation approaches involving reactant control, inhibition of promoter, catalyst or intermediate, and minimising contamination occurrence during refining that should be undertaken to resolve the presence of 3-MCPDE and GE in both cooking oils and oil-based food products. Bognár et al (2020) showed that different chlorinated salts influence the fate of 3-MCPDE in edible oil when subjected to frying.…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
“…The formation of 3-MCPDE, 2-MCPDE, and GE in refined vegetable oils has been studied by several authors, but the mechanism of reaction is still unknown. , Studies suggested that the formation of hydrochloric acid (HCl) resulting from the thermal degradation of chlorinated compounds during the oil refining is a relevant factor in MCPDE formation. Differently, GE is formed as a result of a molecular rearrangement of diacylglycerol (DAG) molecules. Since MCPDE and GE do not share the same formation route, their simultaneous mitigation is still considered a challenge.…”
Section: Introductionmentioning
confidence: 99%